2022
DOI: 10.3390/cancers14051222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neoadjuvant Chemotherapy on Complications, in-Hospital Mortality, Length of Stay and Total Hospital Costs in Bladder Cancer Patients Undergoing Radical Cystectomy

Abstract: Background: To test for differences in complication rates, in-hospital mortality, length of stay (LOS) and total hospital costs (THCs) in patients treated with neoadjuvant chemotherapy (NAC) prior to radical cystectomy (RC). Methods: Within the National (Nationwide) Inpatient Sample (NIS) database (2016–2019), we identified RC-treated, non-metastatic, lymph-node negative bladder cancer patients, stratified by NAC status. Trend analyses, multivariable logistic, multivariable Poisson and multivariable linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Interestingly, in our series, 61% of patients undergoing multimodal treatment receive an ileal neobladder, compared to 31% of those undergoing surgery alone. This pattern aligns with the findings from other studies with a similar design, where patients undergoing NAC are more frequently the chosen candidates for a continent diversion [21,23,24,27,28]. This tendency could be explained by demographic and health status factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, in our series, 61% of patients undergoing multimodal treatment receive an ileal neobladder, compared to 31% of those undergoing surgery alone. This pattern aligns with the findings from other studies with a similar design, where patients undergoing NAC are more frequently the chosen candidates for a continent diversion [21,23,24,27,28]. This tendency could be explained by demographic and health status factors.…”
Section: Discussionsupporting
confidence: 89%
“…Patients undergoing NAC are, on average, younger by about 4 years in the examined series, and generally have fewer comorbidities, despite potential variability in health indicators such as ASA, CCI, and the modified Frailty Index. In such patients, who are more suitable candidates for continent urinary diversion, specialists may feel more confidential in recommending a multimodal therapeutic approach [21,22,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…These observations align with prior investigations, which reported lower NAC utilization rates among cystectomy patients with similar characteristics-notably lower income [20]. A National Inpatient Sample study by Hoen et al found that NAC was associated with shorter length of stay but higher total hospital costs [45]. The cost of NAC administration, in addition to radical cystectomy, estimated at a mean of USD 52,429 by Stevenson et al [46], may present a considerable financial barrier for low-income groups, with potentially adverse consequences on survival.…”
Section: Factors Influencing the Use Of Nac And Plnd In Rcsupporting
confidence: 88%
“…Within the NIS database (2016-2019), we selected patients (aged >18 years) with a primary diagnosis of bladder cancer (International Classification of Disease, Tenth Revision, Clinical Modification [ICD-10-CM] codes C67.0-C67.6, C67.8, C67.9). Of those, patients treated with radical cystectomy were selected relying on Procedure Coding System (ICD-10-PCS), as recently reported and validated by Lyon et al 16,17 ICD-10-PCS codes were also used to distinguish between RARC versus ORC versus laparoscopic RC. 16 Additionally, patients with secondary ICD-10-CM codes indicating lymph-node invasion or metastatic stage were excluded from further analyses.…”
Section: Study Populationmentioning
confidence: 99%